The Impact of Gartic.io-Based Pictionary Game on Students’ English Vocabulary of SMAN 1 Sakra Timur - Laila Nurizmi; Laila Wati; Hajriana Arfah; M. Adib Nazri (Journal on Education, 2024)
The purpose of this research was to determine the impact of Gartic.io-based Pictionary game on English vocabulary of students at SMAN 1 Sakra Timur. This research used a quantitative method with a true experimental design. The population of the research consisted of eleventh-grade students at SMAN 1 Sakra Timur academic year 2024/2025, with a sample was 36 students for two classes, 18 students in the experimental group (XI 1) and 18 students in the control group (XI 2). Data were collected using multiple-choice tests as pre-tests and post-tests to measure English vocabulary improvement. The data analysis technique used was an independent sample T-test conducted via SPSS version 22. The researcher found a significance value (2-tailed) of 0.317. Since 0.317 > 0.05, the alternative hypothesis (Ha) was rejected, and the null hypothesis (Ho) was accepted. Therefore, it can be concluded that the Gartic.io-based Pictionary game does not significantly impact the vocabulary achievement of high school students.